2018
DOI: 10.1055/a-0751-3917
|View full text |Cite
|
Sign up to set email alerts
|

Gesundheit von Asylsuchenden in Bielefeld: eine Querschnitt-Pilotstudie

Abstract: ZUSAMMENFASSUNGSeit 2015 sind viele Flüchtlinge nach Deutschland gekommen, dennoch fehlen adäquate Gesundheitsdaten dieser heterogenen Gruppe. Ziel dieser Querschnitt- Pilotstudie ist es, relevante demografische und gesundheitliche Daten der Asylsuchenden der Erstaufnahmeeinrichtung (EAE) in Bielefeld zu identifizieren. Diese Studie basiert auf der Analyse von Managementdaten der Einrichtung und der Auswertung von 99,6 % der erstellten Gesundheitskarten von 2671 Bewohnern der EAE Bielefeld. Die Studie zeigt, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
1
2
0
1
Order By: Relevance
“…It is concerning that the current system for receiving refugees only identified a small percentage of these cases at the reception centre. The percentage of severe psychological crisis cases identified by the screening was 6.6% which is similar to a comparable study by Niklewski and colleagues (Niklewski et al, 2012 ) and much higher than the percentage of cases detected without a systematic screening for mental health disorders (Van den Heuvel & Stammnitz, 2018 ). However, the results showed that not all severe psychological crises cases were identified as ‘red flags’ through the screening procedure, either.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…It is concerning that the current system for receiving refugees only identified a small percentage of these cases at the reception centre. The percentage of severe psychological crisis cases identified by the screening was 6.6% which is similar to a comparable study by Niklewski and colleagues (Niklewski et al, 2012 ) and much higher than the percentage of cases detected without a systematic screening for mental health disorders (Van den Heuvel & Stammnitz, 2018 ). However, the results showed that not all severe psychological crises cases were identified as ‘red flags’ through the screening procedure, either.…”
Section: Discussionsupporting
confidence: 86%
“…This challenge currently manifests itself in a gap between the legal regulations obliging its representatives to implement measures for the early identification of illness and the provision of adequate health care (e.g. 2013//33/EU), on one side, and the actual practices lacking of a systematic identification procedure as well as of available treatment options, on the other side (Bozorgmehr et al, 2016 ; Bundesweite Arbeitsgemeinschaft der psychosozialen Zentren für Flüchtlinge und Folteropfer [BAfF], 2020 ; Van den Heuvel & Stammnitz, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Die identifizierte Verteilung von Alter und Geschlecht in dieser Arbeit war vergleichbar mit der Verteilung in unserer vorherigen Studie. Ein wichtiger Unterschied bezüglich Nationalitäten war, dass die Türkei nun die "top ten" der Herkunftsländer von Asylsuchenden in Bielefeld anführt [15].…”
Section: Diskussionunclassified